The Association of Spirituality with Self-Management in Post-Stroke Patients: A Cross-Sectional Study - Nur Hidayati; Zanu’ Rizky Wilujeng; Aprelia Afidatul Hanafi; Sugiharto Sugiharto; Suwardi Suwardi (Indonesian Journal of Global Health Research, 2026)
Post-stroke patients tend to experience spiritual distress, characterized by seeking spiritual assistance and expressing excessive doubts about the meaning of life. The problems that arise in self-management among post-stroke patients are primarily caused by decreased independence and mobility, as well as inadequate family support, resulting in unmet patient needs and hindering their ability to manage themselves. To investigate the relationship between spirituality levels and self-management in post-stroke patients. This study employed a cross-sectional design involving 145 post-stroke patients selected through a convenience sampling technique. The study was conducted in June 2025 at Muhammadiyah Hospital Lamongan. The instruments used were the Daily Spiritual Experience Scale (DSES) and the Southampton Stroke Self-Management Questionnaire (SSSMQ) (Cronbach's α 0.94 and 0.90, respectively). The data were analyzed using the Pearson test. The results showed a strong correlation between the level of spirituality and self-management (p = 0.000; r = 0.934), with the highest correlation observed two months after the stroke (r = 0.978). The higher the level of spirituality, the higher the self-management ability of post-stroke patients. These findings highlight the importance of spirituality in promoting self-management among post-stroke patients, thereby improving their quality of life and recovery.